OPTICAL SCATTERING RESONANCES OF SINGLE NOBLE METAL NANOSPHERE - PANDUWIRAWAN (NIM. 10209062), ADISETYO
Metallic nanoparticles have been widely used in nano-scale photonic devices for enhancing their performances or creating novel functionalities due to the highly sen- sitive plasmonic resonance effects. Even since the past, light scattering by metallic nanoparticles have been used until now as the glass staining agent. Recently, variety of useful applications have been reported in the literature, for instance in optical sensing and imaging, photovoltaic cells even medical applications to name just a few. This resonance effect has been intensively studied using Mie theory formula- tion based on non-dissipative Drude model for the refractive index of the nanosphere. In this work, we report the resonance condition on a gold and silver nanospheres of radius a on the basis of maximizing the first order of TM reflection coefficient. We found a modified Frhlich condition of the real part of the nanoparticle permittivity as a function of the size parameter q. The modified Froohlich condition was then fitted to the numerical data deduced from the resonance peaks of the scattering efficiencies (Qscat) of gold and silver nanospheres. The data agree nicely with the deduced approximated analytical relationship above for q < 0.9.